Observation of a gerade symmetry state of Cu2 using two‐color resonant four‐wave mixing. (11th December 2019) - Zhang, Qiang; Bornhauser, Peter; Knopp, Gregor; Radi, Peter
Abstract: The first observation of an excited 0 g + state of dicopper is reported. "g" inversion symmetry states are not observable by direct one‐photon absorption from the X 1 Σ g + ground state. Measurements are performed by applying nonlinear two‐color resonant four‐wave mixing (TC‐RFWM) spectroscopy. Cold Cu2 molecules in a molecular beam environment are generated by applying a pulsed laser vaporization source and subsequent near supersonic expansion of the vaporized metal plume entrained in a helium pulse. Spectra in the wavenumber region of the [37.5( v )]0 g + ‐ B0 u + electronic transition are recorded by using the UNFOLDED double‐resonance scheme. Specific rotational levels of the intermediate state B0 u +, v ′ =1 are accessed from the X 1 Σ g + ground state. Dipole selection rules from the labeled levels define unambiguously the rotational quantum number and symmetry of the final state (Δ J =±0, 1 and g ↔ u). The UNFOLDED scheme is verified by additional measurements via the origin level, v ′ =0, of the intermediate B0 u + state. Spectroscopic constants of the [37.5( v )]0 g + state have been determined for both 63 Cu2 and 63 Cu 65 Cu isotopologues by analysis of the rotationally resolved spectra. The potential of TC‐RFWM to study the unexplored "g" symmetry manifold of Cu2 is discussed.